2010
DOI: 10.1080/08927014.2010.495772
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of various chemical disinfectants on biofilms formed in spacecraft potable water system components

Abstract: Wong, Wing C.; Dudinsky, Lynn A.; Garcia, Veronica M.; Ott, Charlie M.; and Castro, Victoria A., "Efficacy of various chemical disinfectants on biofilms formed in spacecraft potable water system components" (2010 As the provision of potable water is critical for successful habitation of the International Space Station (ISS), life support systems were installed in December 2008 to recycle both humidity from the atmosphere and urine to conserve available water in the Station. In-flight pre-consumption testing fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…In 2010, Wong et al tested disinfectants such as hydrogen peroxide (H 2 O 2 ), colloidal silver, and buffered pH solutions on bacteria isolated from ISS water systems: Ralstonia picketti, Burkholderia multivorans, Caulobacter vibrioides and Cupriavidus pauculus. Results of the experiments showed that a single flush with either 6% H 2 O 2 or a mixture of 3% H 2 O 2 and 400 ppb colloidal silver solution effectively reduced bacterial concentrations for up to three months [9].…”
Section: Biofilm Control Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2010, Wong et al tested disinfectants such as hydrogen peroxide (H 2 O 2 ), colloidal silver, and buffered pH solutions on bacteria isolated from ISS water systems: Ralstonia picketti, Burkholderia multivorans, Caulobacter vibrioides and Cupriavidus pauculus. Results of the experiments showed that a single flush with either 6% H 2 O 2 or a mixture of 3% H 2 O 2 and 400 ppb colloidal silver solution effectively reduced bacterial concentrations for up to three months [9].…”
Section: Biofilm Control Methodsmentioning
confidence: 99%
“…(particularly Sphingomonas paucimobilis ), Cupriavidus spp., Chryseobacterium spp., and Ralstonia spp. [ 8 , 9 , 10 , 11 , 12 ]. Most of the above mentioned bacteria are human-associated, usually found on human skin, and are determined to be responsible for the formation and diversity of spacecraft microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Unwanted biofilm formation causes biofouling of heat exchange systems and marine structures, microbial induced corrosion of metal surfaces, deterioration of dental surfaces, contamination of household products including food and pharmaceuticals as well as the infection of short-and long-term biomedical implants and devices (Hall-Stoodley et al 2004;Choi et al 2010;Tang et al 2011;Teodo´sio et al 2011). Antimicrobial agents have been the main weapons used to control biofilms, acting either by interfering with microbial metabolism or by facilitating their detachment from the surface (Chen and Stewart 2000;Fay¨et al 2010;Wong et al 2010). The target of an antimicrobial strategy is to inactivate and reduce the number of microorganisms and to control the formation of biodeposits on surfaces (Mun et al 2009;Simo˜es et al 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, a minor outbreak was reported in Ohio, in which a clinical microbiology lab identified 27 cases of C. pauculus over six weeks, from a single physician’s office that moistened culture swabs with tap water [12]. Interestingly, C. pauculus was also identified in the International Space Station potable water supplies during pre-consumption testing [13]. Based on these sources and case reports, it is conceivable that C. pauculus contaminated the surgical wound and resulted in a clinically-relevant infection.…”
Section: Discussionmentioning
confidence: 99%